Estimating the schedule delay of marine projects in Turkey deu to pssible delay causes by using bayesian belief network model - Elibol, Ozan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Marine projects have become one of the most fascinating industries in Turkey because of their enormous contribution to the local economic growth. Thereof, the completion of these projects on time has critical importance for the future of Turkey’s economy. In this study, the major delay factors that are encountered in the marine construction industry in Turkey are listed through an exhaustive review of the literature and the ﬁnal delay factors list is approved by the experts. Each delay factors is ranked according to their frequencies by collecting data from the experienced professionals in the industry using a survey. Moreover, the ﬁndings of the survey enable to determine the dependencies between the delay factors by calculating the Pearson Correlation Coeﬃcient of each delay factor pair. Once the dependent delay factors are identiﬁed, the Bayesian Belief Network is drawn so that the path causing delay is determined. By utilizing the correlation coeﬃcients, means and standard deviations of the delay factors, the conditional probability tables are obtained. The implementation of the proposed model is carried out by a case study. The results show that the delay duration of an uninitiated marine project in Turkey can be estimated by utilizing the proposed model. Also, since the dependencies between the delay factors are identiﬁed, the practitioners could deﬁne the cause-eﬀect relations and may prevent the delays by focusing on the origin of the delay factors.
Keywords: Marinas -- Turkey.; Bayesian statistical decision theory.